Forty years later: a new Andean stream treefrog of the genus Hyloscirtus (Anura: Hylidae) from Ecuador, with comments on arm hypertrophy in the H. larinopygion group - Rivera-Correa, Mauricio; Ron, Santiago; Nunes, Ivan [UNESP]; Araujo-Vieira, Katyuscia [UNESP]; Pinheiro, Paulo D.P.; Grant, Taran (Magnolia Press, 2024)
We present the description of a novel treefrog species inhabiting the Andean streams in southeastern Ecuador that has been erroneously identified as Hyloscirtus lindae for four decades. The new species is closely related to H. tapichalaca and is part of the southern clade of the H. larinopygion group, which comprises five species confined to the southeastern Andes of Ecuador to the northeastern Andes of Peru. It is diagnosed from its close relatives by a unique combination of characteristics, including hypertrophied forelimbs in males, a pronounced, curved, and protruding spine-shaped prepollex, a substantial supracloacal flap, supratympanic fold, digital discs colored in shades of orange-red or bright-red, and the concealed surfaces of limbs displaying a bluish-gray hue and dorsal spicules in males. We briefly explore the implications of this discovery for the evolution of arm morphology in the H. larinopygion group. Our findings underscore the continued importance of periodically reviewing historical specimens, leading to unexpected discoveries; once again confirming the importance of natural history museums and their custodian biological collections.
Keywords: Andes; Biodiversity; Biological Collections; Morphology; Systematics; Taxonomy